Cause and Effect Relationship for Some Biometric Traits in Bread Wheat - Cheema, Nazar Muhammad; Mian, Muhammad Ashraf; Ihsan, Muhammad; Tariq, Muhammad Azeem; Rabbani, Ghulam; Mahmood, Abid (Biological Sciences - PJSIR, 2005)
Genotypic and phenotypic correlations and path coefficient analyses were conducted for grain yield and some biometric traits in 25 cross-combinations of bread wheat under the rainfed conditions. Significant positive geno- typic and phenotypic association was observed between grain yield per plant, and the yield components, such as productive tillers per plant, spike-length, spikelets per spike, grains per spike and 1000-grain weight. The path coeffi- cient analysis revealed that the number of grains per spike and 1000-grain weight had the maximum direct effect on grain yield. These traits may be considered as the selection criteria for developing high yielding wheat genotypes for rainfed areas.